Credulism - Kvanvig, Jonathan L. (International journal for philosophy of religion, 1984)
The credulity principle approach to the issue of the rationality of religious belief is a clear advance over the proof approach. For the proof approach, in the end, is simply too wedded to an infallibilist conception of rational belief; and initially, at least, the credulity principle approach seems to avoid this conception. In the end, however, it affirms that same viewpoint; for if it does not embody an infallibilist conception of epistemic principles, its critical property of intersubjectivity is beyond defense. Thus, in recognizing the inadequacy of infallibilist conceptions of rationality, we can see the inadequacy of both the proof approach and the credulity principle approach to the existence of God. It is simply false that the experiences of others is efficacious in conferring rationality on our beliefs., But if neither of these approaches is adequate, how is one to approach the issue of the rationality of religious belief? The subjective nature of rational belief provides the answer - if one wishes to argue that God exists, one will have to provide as many arguments as there are divergent sets of acceptable epistemic principles. There still is a place for such arguments; but only given the assumption that we share views about what sorts of inferences are proper, or that other arguments can be constructed for the superiority of certain epistemic principles. The view that must be given up, however, is that the discussions philosophers have of these issues need bear any relation to whether or not the normal religious believer has a reasonable belief or not - he does not need there to be a good philosophical argument that God exists in order to reasonably believe that God exists. Nor is any non-believer necessarily irrational just because there is such a good argument., Thus, once the nature of rational belief is properly appreciated, it appears that the question of the rationality of religious belief is not a central question any longer. Whether such beliefs are rational is a quite subjective question not capable of being answered by any sort of universal generalization about all religious believers and/or non-believers.